DEPENDENCE OF MILK PRODUCTION OF MONBELYARD COWS ON THE CHARACTERISTICS OF BODY STRUCTURE - Utkir Rajabovich Soatov; Guzal Mirulugovna Erdanova; Ulugbek Erkulov (Journal Park Publishing, 2022)
This article provides information on the characteristics of increasing the weight of cows in the direction of milk productivity in herds and improving the efficiency of using cows by selecting and mating the Montbelyard cows brought from France, taking into account the types of body structure.
Keywords: Montbelyard breed, cow, milk, milk fat, milk protein, dry matter, 4% milk, milk-meat, meat-milk, body structure, exterior.